2016
DOI: 10.3389/fnhum.2016.00044
|View full text |Cite|
|
Sign up to set email alerts
|

The Influence of Menstrual Cycle and Androstadienone on Female Stress Reactions: An fMRI Study

Abstract: Communicating threats and stress via biological signaling is common in animals. In humans, androstadienone (ANDR), a synthetic male steroid, is a socially relevant chemosignal exhibited to increase positive mood and cortisol levels specifically in (periovulatory) females in positively arousing contexts. In a negative context, we expected that such effects of ANDR could amplify social evaluative threat depending on the stress sensitivity, which differs between menstrual cycle phases. Therefore, this fMRI study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 64 publications
(110 reference statements)
4
19
0
Order By: Relevance
“…Based on similar procedures performed in our group [34, 35], a 250μM solution of AND (purity of AND ≥ 99%; Steraloids Inc., Newport, RI, USA) was prepared, diluted in propylene glycol and masked with 1% musk oil (Sigma–Aldrich, Deisendorf, Germany; please refer to S4 Text for the exact chemical composition of the musk oil used). This concentration close to detection threshold [36] has been shown to increase autonomic arousal in women [37].…”
Section: Methodsmentioning
confidence: 99%
“…Based on similar procedures performed in our group [34, 35], a 250μM solution of AND (purity of AND ≥ 99%; Steraloids Inc., Newport, RI, USA) was prepared, diluted in propylene glycol and masked with 1% musk oil (Sigma–Aldrich, Deisendorf, Germany; please refer to S4 Text for the exact chemical composition of the musk oil used). This concentration close to detection threshold [36] has been shown to increase autonomic arousal in women [37].…”
Section: Methodsmentioning
confidence: 99%
“…Data regarding sex differences in hippocampal activation during psychosocial stressors are however limited and inconsistent. While some studies report higher activation in men ( Kogler et al, 2017 ; Seo et al, 2011 ), others report higher activation in women ( Kogler et al, 2015 ; Abercrombie et al, 2011 ), particularly women during their luteal cycle phase ( Chung et al, 2016 ; Chung et al, 2016 ). Furthermore, in women stronger hippocampal activation was related to increased subjective stress ratings ( Kogler et al, 2015 ; Chung et al, 2016 ).…”
Section: Neuroimaging Studies On the Effects Of Sex And Stress Hormonmentioning
confidence: 98%
“…Our female subjects participated in the study during their luteal phase. As previous studies showed that amygdala activation in response to psychological stressor depends on menstrual cycles (Chung et al, 2016) and that cortisol responses to social stress are comparable between females in a luteal phase and males (Kirschbaum et al, 1999), we investigated on female participants only in their luteal phase. However, no conclusion regarding the neural responses is drawn from the current study.…”
Section: Discussionmentioning
confidence: 99%